Penyelesaian Pembiayaan Bermasalah Pada Akad Murabahah dI PT. Bank SUMUT Syariah KCP Stabat Menurut Fatwa DSN MUI - Hafis, Muhammad Hafis; Muhizar Muchtar (Peduli Riset dan Pengabdian Masyarakat, 2022)
This study focuses on the discussion on the implementation of murabahah contract financing, the settlement of troubled murabahah contract financing at PT. Bank SUMUT Syariah KCP Stabat which is then analyzed and compared with the DSN MUI Fatwa regarding the settlement of problematic financing. The research method used in this study is a descriptive qualitative research method with an empirical approach. The results of the study explain that the implementation of murabahah contract financing at PT. Bank SUMUT Syariah KCP Stabat is almost the same as financing in general, namely starting with an application, survey and disbursement. Settlement of troubled murabahah contract financing at PT. Bank SUMUT Syariah KCP Stabat, namely intensive billing, giving warning letters, rescheduling, writing off, and the last is the execution of guarantees. Overall, the completion of problematic murabahah financing at PT. Bank SUMUT Syariah KCP Stabat is in accordance with the DSN MUI Fatwa, from the stage of intensive summons to execution of guarantees in line with the DSN MUI Fatwa, but regarding the release of customers who really are no longer able to pay off their financing payments even after the execution of guarantees is not carried out by PT. Bank SUMUT Syariah KCP Stabat because debt is something that customers still have to pay and avoid similar things being imitated by other customers